PERANCANGAN MEDIA PROMOSI KLINIK Dr. DHANY SEBAGAI UPAYA MENINGKATKAN BRAND AWARENESS - Putri, Shella Febryani Cantika; Dewanto, Thomas Hanandry; Yosep, Sigit Prayitno (Jurnal Art Nouveau, 2014)
The clinic of Dr. Dhany beauty clinic is one of the new stand in Surabaya. It became the basis of the establishment of the clinic is due to the growing trend of beauty industry in Indonesia. Beauty Clinic Dr. Dhany was founded by Dr. N.A. Kusumawardani and was founded on August 1, 2013 and set on the road No. 18 Supreme Karah Surabaya. The clinic is in excess is the material used in this clinic uses natural ingredients or herbs in addition the clinic also provides a slimming treatment that is safe for the body. But the clinic has not been doing promotional activities and rely solely on word of mouth promotion, this causes yet aware and yet familiar Clinic Dr. Dhany. The problems that have occurred in a beauty clinic Dr. Dhany is a new clinic, do not have a media promotions can provide information to the public in order to increase awereness brand Clinic Dr. Dhany.